Thermal Stabilization of Permafrost Using Thermal Coils Inside Foundation Piles - Alexander Lavrik; George Buslaev; Mikhail Dvoinikov (Civil Engineering Journal, 2023)
The article deals with the issue of thermal stabilization of soils to preserve the stability of pile foundations in permafrost conditions. The purpose of the work is to develop a technology for year-round freezing of soils by supplying coolant cooled by a refrigeration machine to thermal elements placed inside piles. In this work, the temperature regime of the system "pile foundation – soil" in the stationary formulation of the problem was simulated, and the influence of the depth of placement of thermal elements inside the piles on the soil temperature was investigated. The simulation was performed in the COMSOL software environment, taking into account the heat transfer due to thermal conduction and convection. In the presented model, a platform is fixed on piles, and a heat source is placed on the platform. It is found that an area of thawed soil has formed on the leeward side of the pile foundation. It is concluded that, under certain conditions, deep thermal elements for freezing or keeping the soil frozen should be placed at different depths. Thus, under given conditions, a greater depth of the thermal element placement in the pile, closest to the soil thawing zone, allows to reduce the surface temperature of the pile below ground level and, therefore, increase its bearing capacity. The authors also propose an original unit for soil thermostabilization based on the absorption cooling machine, which can operate at the expense of thermal energy generated by technological sources located on the platform. Doi: 10.28991/CEJ-2023-09-04-013 Full Text: PDF